PENGARUH BEBAN KERJA, KOMUNIKASI DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PT. TIRTA VARIA INTIPRATAMA - Hardianto, Shony; Sitorus, Guston; Wahyono, Agus (Jurnal Manajemen, 2025)
This study aims to analyze the effect of workload, communication, and work culture on employee performance with work motivation as an intervening variable at PT. Tirta Varia Intipratama. Employee performance is a crucial aspect in achieving company goals, where factors such as workload, communication, and work culture can affect the level of employee motivation and productivity. The research method used is a quantitative approach with path analysis techniques. Data were collected by distributing questionnaires to employees of PT. Tirta Varia Intipratama. The results of the study indicate that workload, communication, and work culture have a significant effect on work motivation. In addition, work motivation is proven to be an intervening variable that strengthens the relationship between these factors and employee performance. These findings provide implications for company management to pay more attention to workload balance, improve effective communication, and build a positive work culture in order to improve employee motivation and performance.